Optimising expression and extraction of recombinant proteins in plants - Coates, Ryan J.; Young, Mark T.; Scofield, Simon (Frontiers in Plant Science, 2022)
Recombinant proteins are of paramount importance for research, industrial and medical use. Numerous expression chassis are available for recombinant protein production, and while bacterial and mammalian cell cultures are the most widely used, recent developments have positioned transgenic plant chassis as viable and often preferential options. Plant chassis are easily maintained at low cost, are hugely scalable, and capable of producing large quantities of protein bearing complex post-translational modification. Several protein targets, including antibodies and vaccines against human disease, have been successfully produced in plants, highlighting the significant potential of plant chassis. The aim of this review is to act as a guide to producing recombinant protein in plants, discussing recent progress in the field and summarising the factors that must be considered when utilising plants as recombinant protein expression systems, with a focus on optimising recombinant protein expression at the genetic level, and the subsequent extraction and purification of target proteins, which can lead to substantial improvements in protein stability, yield and purity.